2018
DOI: 10.1007/s10803-018-3643-5
|View full text |Cite
|
Sign up to set email alerts
|

Leisure Participation Patterns for School Age Youth with Autism Spectrum Disorders: Findings from the 2016 National Survey of Children’s Health

Abstract: Leisure activity participation is important for health and well-being. This study examined similarities and differences between typically developing children and those with autism spectrum disorders (ASD) from 6 to 17 years old in physical, recreational, social, skill, and jobs/chores activities from a large national database. Findings revealed that children with ASD had significantly lower participation levels than those without ASD between 11 and 17 years old. They suggest an increasing disparity among many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 39 publications
1
22
2
Order By: Relevance
“…Children at Y3 reported to get together with other people across contexts less frequently than reported at Y1 and Y2. This decline with increasing age in overall social participation is in contrast with the findings from Ratcliff et al () who reported a generally stable pattern of social activities participation between ages 6–15 years. Ratcliff et al's findings were based on a composite score and as such may not have reflected participation changes within types of social activities as reported in this study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Children at Y3 reported to get together with other people across contexts less frequently than reported at Y1 and Y2. This decline with increasing age in overall social participation is in contrast with the findings from Ratcliff et al () who reported a generally stable pattern of social activities participation between ages 6–15 years. Ratcliff et al's findings were based on a composite score and as such may not have reflected participation changes within types of social activities as reported in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…The decline in participation in physical activities (organized and unstructured) with age is consistent with previous research on children on the autism spectrum (Jones et al, ; Ratcliff et al, ) and their typically developing peers (Dumith, Gigante, Domingues, & Kohl, ). There was a decrease in the number of children involved in organized physical activities from Y1 ( n = 51; 60.7%) to Y3 ( n = 39; 46.4%).…”
Section: Discussionsupporting
confidence: 88%
“…These tasks are needed to successfully gain and sustain employment, care for oneself and become one's own advocate (Lindsay et al, 2015). Finally, the three themes identified in this study are valuable because they potentially play a role in shaping the leisure preferences and behaviors of the youth over their lifespan, depending on the severity of the disability and the availability of family and community support systems (Johnson & Bagatell, 2017;Ratcliff, Hong, & Hilton, 2018…”
Section: Value Of the Themesmentioning
confidence: 92%
“…The transition from adolescence to adulthood is a crucial time of change in most people's lives, bringing dramatic transformation of virtually every major life domain. The phase of life coined emerging adulthood (approximately ages [18][19][20][21][22][23][24][25] is characterised by opportunities to explore roles and relationships [1], but also increased demands on independence and associated risks such as unemployment, truncated education, dependence on parents, loneliness, onset of mental health conditions, and sedentary lifestyles [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…This group of young people also tend to participate less than their peers in activities (e.g. physical activities, job, and chores) that contribute to adult competencies [21,22]. This mix of functional impairments, insufficient support, and lack of structured activities leaves the individual at risk of inactivity and social isolation.…”
Section: Introductionmentioning
confidence: 99%